Drug-Related Problems Among Ambulatory Heart Failure Patients on Follow-Up at Debre Berhan Comprehensive Specialized Hospital, Ethiopia - Tsige AW; Yikna BB; Altaye BM (Dove Medical Press, 2021)
Abate Wondesen Tsige,1 Berhan Begashaw Yikna,2 Birhanetensay Masresha Altaye2 1Clinical Pharmacy Unit, Department of Pharmacy, College of Health Sciences, Debre Berhan University, Debre Berhan, Ethiopia; 2Pharmacology and Toxicology Unit, Department of Pharmacy, College of Health Sciences, Debre Berhan University, Debre Berhan, EthiopiaCorrespondence: Abate Wondesen Tsige Tel +251 921126837Fax +251 116812065Email Abatewondesen@dbu.edu.etPurpose: The purpose of this study was to assess drug-related problems (DRPs) among ambulatory heart failure (HF) patients attending at medical referral clinic of Debre Berhan Comprehensive Specialized Hospital, Ethiopia.Materials and Methods: A hospital-based cross-sectional study was conducted among 344 HF patients. Drug-related problems were classified using modified Cipolle's DRP classification schemes and drug-drug interactions were assessed using Micromedex, up-to-date, and drug.com drug-drug interaction checkers. The data was entered into Epidata version 4.2.0 and analyzed using SPSS version 25.0 statistical software. Descriptive statistics were used to summarize patients' characteristics. Univariable and multivariable binary logistic regression analysis was performed to identify associated factors with dependent variables. P < 0.05 was considered statistically significant.Results: The mean age of the study participants was 53.38 ± 18.84 years and nearly half (45%) were in the age group of 31- 60 years. Drug-related problems were found in 80.8% of HF patients. A total of 416 DRPs were identified. Adverse drug reaction (35.58%) was the top DRPs identified followed by the need for additional drug therapy (30.53%) and ineffective drug therapy (26.9%), respectively. Diuretics (45%), beta-blockers (BBs) (12.42%), and angiotensin-converting enzyme inhibitors (ACEIs) (10%) were the commonly used drug classes by study participants. The presence of comorbidity (p ˂ 0.001) and level of education of study participants (p = 0.03) had a significant association with the occurrence of DRPs.Conclusion: The prevalence of DRPs among ambulatory HF patients was high. The presence of comorbidity and the educational level of study participants had a significant association with the occurrence of DRPs. Checking potential drug-drug interactions before starting a new therapy, monitoring adverse drug reactions, ensuring sustainable availability of medications, and regular education programs are recommended to minimize DRPs.Keywords: heart failure, drug-related problem, Cipolle's DRP classification scheme, Ethiopia